Politik Hukum Hak Asasi Manusia dalam Negara Hukum Demokratis Indonesia - Fajar Setiawan; Anggraeni Fuspita Dewi; Farhan Mubarok; Sugianto; Tarmudi (PEPAKEM: JURNAL HUKUM TATA NEGARA DAN POLITIK ISLAM, 2025)
Legal policy determines the direction of lawmaking, implementation, enforcement, and institutional reform, while human rights serve as both the limit and the objective of state power. This study analyzes the relationship between legal policy and human rights within Indonesia’s democratic rule-of-law framework. It employs normative legal research using statutory, conceptual, historical, and case approaches. Primary legal materials include the 1945 Constitution, Law Number 39 of 1999, Law Number 26 of 2000, the statutes ratifying the ICCPR and ICESCR, legislation on lawmaking, and Constitutional Court decisions concerning meaningful participation. Secondary materials consist of scholarly books and journal articles on legal policy, constitutionalism, and human rights. The materials are qualitatively analyzed through grammatical, systematic, historical, and teleological interpretation. The findings show that human-rights-oriented legal policy operates through four interconnected stages: norm formation based on human dignity, implementation limited by legality and proportionality, constitutional and judicial supervision, and effective remedies for victims. Indonesia has developed a relatively strong constitutional and institutional foundation, but inconsistencies remain between normative guarantees and legislative or administrative practice. Security, development, majoritarian interests, weak participation, and discriminatory enforcement may reduce substantive protection. Democratic legal policy must therefore apply constitutional review, meaningful participation, proportionality, non-discrimination, and effective remedies as mandatory standards for every public policy.